KEYS TO SUCCESS IN THE DIGITAL ECONOMY: STRATEGIES AND POLICIES SHAPING THE FUTURE OF THE INDUSTRY - Loso Judijanto (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
In the digital economy era, the success of an entity is largely determined by the strategies and policies implemented to respond to the dynamics of technological and market changes. This article examines various approaches that can be taken by the government and the private sector to sustain the growth of the digital economy, including the development of digital infrastructure, the enhancement of digital skills, and the implementation of balanced regulations. In addition, international co-operation and a focus on research and innovation are identified as key factors in shaping a competitive and inclusive industry ecosystem. Thus, by applying a proactive and comprehensive strategy, the future success of the digital economy can be achieved, forming a strong foundation for sustainable growth.